ARTERIAL STIFFNESS AND CHRONIC KIDNEY DISEASE: CAUSES AND CONSEQUENCES - J. D. Kobalava; Yu. V. Kotovskaya; S. V. Villevalde; A. E. Soloveva; I. M. Amirbegishvili (Рациональная фармакотерапия в кардиологии)
Chronic kidney disease (CKD) is associated with increased cardiovascular risk. CKD is characterized by accelerated aging of vessels in which the age-related arterial stiffness increase is exacerbated by a number of uremia-related processes. Increased arterial stiffness is associated with structural and functional disorders, as well as with the increase in cardiovascular mortality in patients with CKD. Increased arterial stiffness is diagnosed at an early stage of CKD. Modern understanding of the mechanisms of increased risk of cardiovascular complications in CKD, the factors contributing to the loss of elasticity of the arteries, arterial stiffness increase consequences are analyzed. Data illustrating the twoway interaction between CKD and arterial stiffness and mechanisms of accelerated progression of arterial stiffness in CKD are presented.